Description of the nymphs of Triatoma pintodiasi Jurberg, Cunha & Rocha, 2013 (Hemiptera: Reduviidae: Triatominae) - Da Motta, Flávia Souza; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2015)
Triatoma pintodiasi Jurberg, Cunha & Rocha, 2013 has been recently described based on material collected on Rio Grande do Sul State, Brazil. Nymphs of this species were unknown and their description might contribute for studies concerning the taxonomy, phylogeny, and evolution of the genus Triatoma. Such description is herein presented, along with comparison with other species of the rubrovaria subcomplex of species.